Alternative translocation of protons and halide ions by bacteriorhodopsin. - Dér, A (1991)
Bacteriorhodopsin (bR568) in purple membrane near pH 2 shifts its absorption maximum from 568 to 605 nm forming the blue protein bRacid605, which no longer transports protons and which shows no transient deprotonation of the Schiff base upon illumination. Continued acid titration with HCl or HBr but not H2SO4 restores the purple chromophore to yield bRHCl564 or bRHBr568. These acid purple forms also regain transmembrane charge transport, but no transient Schiff base deprotonation is observed. In contrast to bR568, no rate decrease of the bRacidpurple transport kinetics is detected in 2H2O; however, the transport rate decreases by a factor of approximately 2 in bRHBr568 compared with bRHCl564. The data indicate that in the acid purple form bR transports the halide anions instead of protons. We present a testable model for the transport mechanism, which should also be applicable to halorhodopsin.